Use of time-lapse resistivity tomography to determine freshwater lens morphology - Baharuddin, M.F.T.; Ismail, Z.; Othman, S.Z.; Taib, S.; Hashim, Roslan (2013)
Time-lapse electrical resistivity tomography (TLERT) was used to determine the freshwater-lens morphology in local scale at Carey Island, Selangor, Malaysia. TLERT images with geological background formation history, borehole and hydraulic conductivity data were used to interpret the changes of morphology. Subsurface resistivity changes were measured by ABEM Terrameter SAS4000 and ES10-64 electrode selector. TLERT monitoring using resistivity images on tide increment shows the freshwater lens morphology exhibited a thin and thick layer side by side of 400 m length of resistivity survey line. The occurrences of heterogeneous alluvium sediments in local scale created the different variability of hydraulic conductivity. The asymmetry of the freshwater lens enabled the tide force increment to pass through the differences in hydraulic conductivity. This is a major factor determining the morphology of freshwater lens in local scale. The results can assist in planning a strategy for sustainable groundwater exploration of local scale at the limited recharge area.